2006
DOI: 10.1021/jf0620261
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Capsaicin and Dihydrocapsaicin in Capsicum Fruits by Liquid Chromatography−Electrospray/Time-of-Flight Mass Spectrometry

Abstract: A simple, highly selective, sensitive, and reproducible liquid chromatography-electrospray ionization/ time-of-flight mass spectrometry method has been developed for the direct and simultaneous determination of capsaicin and dihydrocapsaicin in Capsicum fruit extracts. Capsaicin and dihydrocapsaicin are the two major members of the so-called capsaicinoid family, which includes other minor analogues, and usually account for at least 90% of the pungency trait in Capsicum fruits. Chromatographic separation of cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 45 publications
5
59
2
1
Order By: Relevance
“…In these varieties, capsaicin concentration ranged between 22 mg/kg and 66.87 mg/kg, and dihydrocapsaicin concentration between 36 mg/kg and 77.12 mg/kg. These results support the findings by Cisneros-Pineda et al (2007), and Garces-Claver et al (2006) who found that some C. annuum cultivars contain higher concentrations of dihydrocapsaicin than the amounts found in C. chinense (Habanero). Ancho pepper showed a low capsaicinoids' concentration with a similar content of capsaicin and dihydrocapsaicin (42.82 mg/kg and 42.19 mg/kg, respectively).…”
Section: Capsaicinoids Of Chili Pepperssupporting
confidence: 91%
“…In these varieties, capsaicin concentration ranged between 22 mg/kg and 66.87 mg/kg, and dihydrocapsaicin concentration between 36 mg/kg and 77.12 mg/kg. These results support the findings by Cisneros-Pineda et al (2007), and Garces-Claver et al (2006) who found that some C. annuum cultivars contain higher concentrations of dihydrocapsaicin than the amounts found in C. chinense (Habanero). Ancho pepper showed a low capsaicinoids' concentration with a similar content of capsaicin and dihydrocapsaicin (42.82 mg/kg and 42.19 mg/kg, respectively).…”
Section: Capsaicinoids Of Chili Pepperssupporting
confidence: 91%
“…Capsaicinoids produce a burning sensation by activating sensory neurons that alert the central nervous system of noxious stimuli. Thus, capsaicinoids, particularly capsaicin, and dihydrocapsaicin are responsible for 90% of the pungency of peppers (Garcés-Claver et al, 2006). Besides their sensory importance, capsaicinoids exert several biofunctional activities.…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical methods have been applied to determine capsaicin or/and dihydrocapsaicin in various samples, such as high-performance liquid chromatography (HPLC) [19], gas chromatography-mass spectrometry (GCÀMS) [6], liquid chromatography-mass spectrometry (LCÀMS) [20], capillary electrophoresis (CE) [21], LC-ESI/MS/MS [22]. Electrochemical techniques, such as the voltammetric ones, are a promising alternative to classical approaches due to their relatively low operational cost, good miniaturization potential, and rapid and sensitive detection procedures, which are suitable for faster analyses.…”
Section: Introductionmentioning
confidence: 99%